Comment on - Ucar, A. (Elsevier Science Bv, 2008)
The purpose of this Letter is to give the reference for the model proposed in the discussion section of the above paper [J.C. Sprott, Phys. Lett. A 366 (2007) 397] and to show that chaotic behavior of this model has been studied in [A. Ucar, Int. J. Eng. Sci. 40 (2002) 25 1; A. Ucar, Chaos Solitons Fractals 16 (2003) 187]. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Prototype; Bifurcation; Behavior